Instructional Leadership in Action: A Case Study on the Role of Teacher Leader in Improving Learning Quality - Ruslan Ruslan; Muhammad Kristiawan; Asti Putri Kartiwi (Journal of Social Work and Science Education, 2026)
While the Indonesian Teacher Leader program is a key policy initiative, empirical research on its direct impact on classroom learning quality is scarce. This qualitative case study at SMA Negeri 1 Bengkulu Selatan employed interviews, observations, and document analysis to explore the roles of Teacher Leaders. Findings reveal that Teacher Leaders perform five key roles: learning leader, coach, collaboration driver, promoter of student agency, and facilitator of professional communities. These roles significantly enhanced differentiated instruction, teacher collaboration, and student-centered learning. The study concludes that the Teacher Leader program, when implemented effectively, is a powerful lever for improving learning quality and fostering a collaborative school culture. The novelty of this study lies in its in-depth exploration of how Teacher Leaders translate policy into classroom practices in the Indonesian context. The practical implication is that schools should strengthen professional learning communities and student leadership programs to maximize the impact of Teacher Leaders. This research contributes to the limited body of literature on teacher leadership in Southeast Asia by providing empirical evidence of its role in enhancing instructional quality and collaborative culture.